2021
DOI: 10.1021/acs.langmuir.1c01346
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of Selenium Nanospheres of Tunable Size and Colloidal Stability with Simple Diketones

Abstract: Temporal and spatial segregations are two fundamental requirements for the successful synthesis of nanoparticles (NPs). To obtain colloidally stable selenium nanospheres (SeNSs), surfactants or polymers are generally needed as structure-directing agents or stabilizers in the reduction approaches for SeNP synthesis. The addition of such chemicals sacrifices the purity of the obtained SeNPs and, therefore, is detrimental to the applications. Here, for the first time, we report that low-molecular weight (less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It is reported that UV/AA is feasible for tunable synthesis of Se nanospheres by regulating either the light intensity or the concentration of AA. 22 In the photochemical processes, BD shares some similarity with AA. 38 We expect that the UV/BD approach should have a good tunability for the generation of Te nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is reported that UV/AA is feasible for tunable synthesis of Se nanospheres by regulating either the light intensity or the concentration of AA. 22 In the photochemical processes, BD shares some similarity with AA. 38 We expect that the UV/BD approach should have a good tunability for the generation of Te nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The two peaks in the XPS spectrum of the obtained particles were identical to those of Te 0 (Figure d). , These results demonstrate the potential of the UV/BD method for Te resource recovery. It is reported that UV/AA is feasible for tunable synthesis of Se nanospheres by regulating either the light intensity or the concentration of AA . In the photochemical processes, BD shares some similarity with AA .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations